Public policy support for agroecology in Latin America: Lessons and perspectives - Jean-François Le Coq; Éric Sabourin; Muriel Bonin; Sandrine Fréguin Gresh; Jacques Marzin; Paulo Niederle; Maria Mercedes Patrouilleau; Luis Vásquez (Global Journal of Ecology - Peertechz Publications, 2020)
Latin American agroecology proposes a transformation of conventional agri-food systems. It is driven by social movements that have succeeded in forming coalitions that have promoted its integration into public policies. These policies involve a range of instruments that are often embedded in programs that also support organic agriculture and sustainable agriculture. However, while these two types of agriculture propose more ecological practices, they do not question the basis of the conventional agri-food system. The implementation of instruments to support agroecology therefore depends on the power relations established within each country. This paper analyses these policies and their influence on the development of agroecology in eight countries: Argentina, Brazil, Chile, Costa Rica, Cuba, El Salvador, Mexico, and Nicaragua. These policies remain fragile, while support for large-scale conventional agriculture is still predominant. Their challenge is therefore to convince more broadly farmers, consumers and policymakers about the importance of issues such as public health and food security.